Dual-pool, three-phase kinetic model of anaerobic digestion in batch mode. Issue 3 (March 2022) - Gouveia, Bruno; Duarte, Elizabeth; dos Santos, Aires; Fernandes, Edgar
Highlights: Original model based on the kinetics of the digestion process. Better performance than current empirical approaches. Interesting tool to reduce the duration of batch tests. Abstract: The ability of anaerobic digestion to create value from waste gives it an important role in reducing greenhouse gas emissions and in the transition to a circular economy. For a better understanding of the digestion process and in order to reduce the number of time-consuming batch tests, an analytical model was developed to describe the kinetics of biogas production. Assuming that the organic fraction of the substrate has different degradation rates, the whole process was modelled as two groups of 1 st order reactions. The model was tested with published data and showed an excellent performance in reproducing the experimental information. Moreover, its kinetic constants provided a useful insight into the internal processes of anaerobic digestion and the substrate characteristics. Given its accuracy in fitting the data, the model can be used as an auxiliary tool to determine the biogas potential, presenting itself as the most complete empirical model currently available. Abstract : Kinetic model; Anaerobic digestion; Bioreactor; Biogas production; Batch mode